Mapping of Land Surface Deformation Using Ps-Insar for Disaster Risk Management in the Future - Kumalawati, Rosalina; Ali, Syamani D; Yuliarti, Astinana; Raharjo, Jany Tri; Rijanta, Rijanta; Saputra, Erlis; Susanti, Ari; Budiman, Puput Wahyu; Anggraini, Rizky Nurita (Universitas Negeri Medan, 2024)
DKI Jakarta is experiencing land subsidence due to overexploitation of its use and the increasing population. It is feared that this decline or deformation will occur in the location of the new national capital. The research objective is